แนวทางการพัฒนาภาวะผู้นำทางวิชาการของผู้บริหารศูนย์การศึกษาพิเศษ ในกลุ่มเครือข่ายส่งเสริมประสิทธิภาพศูนย์การศึกษาพิเศษ เครือข่ายที่ 9 - ไชยวงศ์คต, วรวุฒิ; เปี่ยมพืชนะ, นิยดา (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 2 (2567): พฤษภาคม – สิงหาคม 2567, 2024)
การวิจัยครั้งนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์ และความต้องการจำเป็นของภาวะผู้นำทางวิชาการของผู้บริหารศูนย์การศึกษาพิเศษ และ 2) เพื่อศึกษาแนวทางการพัฒนาภาวะผู้นำทางวิชาการของผู้บริหารศูนย์การศึกษาพิเศษ การวิจัยแบ่งออกเป็น 2 ระยะ  คือ ระยะที่ 1 ศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์ และความต้องการจำเป็น กลุ่มตัวอย่างที่ใช้ในการวิจัยคือ ผู้บริหารและครู จำนวน 222 คน เครื่องมือที่ใช้ คือ แบบสอบถามมาตรประมาณค่า 5 ระดับ สถิติที่ใช้ คือ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และดัชนีความต้องการจำเป็น ระยะที่ 2 สร้างแนวทางการพัฒนา จากสถานศึกษาที่มีการปฏิบัติดี จำนวน 3 แห่ง ผู้ให้ข้อมูล คือ ผู้บริหารและครู  จำนวน 18 คน เครื่องมือที่ใช้ คือ แบบสัมภาษณ์กึ่งโครงสร้างและประเมินความถูกต้อง ความเหมาะสม และความเป็นไปได้ สถิติที่ใช้ คือ ค่ามัธยฐาน ค่าพิสัยระหว่างคลอไทล์ ผลการวิจัยพบว่า 1) สภาพปัจจุบัน โดยภาพรวมอยู่ในระดับปานกลาง สภาพที่พึงประสงค์ โดยภาพรวมอยู่ในระดับมากที่สุด และลำดับความต้องการจำเป็น เมื่อพิจารณารายด้าน ด้านที่มากที่สุด คือ ด้านการนิเทศการสอน และด้านที่น้อยที่สุดคือด้านการประเมินผลและตรวจสอบความก้าวหน้าของนักเรียน 2) แนวทางการพัฒนาภาวะผู้นำทางวิชาการ ความถูกต้อง ความเหมาะสม และความเป็นไปได้อยู่ระดับมาก โดยมีแนวทางการพัฒนา คือ (1) ด้านการวางแผนกำหนดภารกิจ ควรศึกษาความสามารถของบุคลากรเพื่อวางแผนต่างๆ ให้บุคลากรทำหน้าที่อย่างสุดความสามารถ  (2) ด้านการจัดการหลักสูตรและการสอน ควรศึกษาบริบทของศูนย์ หลักสูตร และปลูกฝังนักเรียนในเรื่องวิชาชีพให้ปฏิบัติได้จริง (3) ด้านการนิเทศการสอน ควรมีการนิเทศให้คำแนะนำครู เพื่อการพัฒนานักเรียนและนำปัญหาต่างๆ ที่พบ มาวิเคราะห์แก้ไข (4) ด้านการประเมินผลความก้าวหน้าของนักเรียน ควรมีการทดสอบทักษะของนักเรียน เน้นให้ครูวัดประเมินผลนักเรียน ตามระเบียบปฏิทินที่ฝ่ายวิชาการกำหนด และ (5) ด้านการส่งเสริมบรรยากาศทางวิชาการ ควรสนับสนุนรางวัลและให้กำลังใจแก่บุคลากร โดยการประชาสัมพันธ์บุคคลากรที่ประสบความสำเร็จ ตามสื่อต่าง ๆ และให้ขยายผลการดำเนินงานภายในสถานศึกษา   The objectives of this research were 1) to study the current situation, the current conditions and needs for academic leadership of Special Education Bureau administrators and 2) to study guidelines for developing academic leadership of Special Education Bureau administrators. The research was divided into 2 phases: Phase 1: Study on the current situation, the current conditions and needs. The sample group used in the research included administrators and teachers, with the total number of 222 people. The instrument used in the research was a 5-level rating scale questionnaire. The statistics used in data analysis comprised mean, standard deviation and priority needs index. Phase 2: Creating guidelines for the development, the informants were administrators and teachers from 3 schools with best practice, with the total number of 18 people. The tools used in the research were semi-structured interview form and assessment form for accuracy, appropriateness, and possibility. The statistics used in data analysis comprised median, interquartile range. The research results were found that: 1) The current situation, in overall, was rated at a moderate level, the current conditions, in overall, was rated at the highest level, for order of needs, when considering each aspect, it was found that the aspect with the highest average of needs was teaching supervision, and the aspect with the lowest average was students’ progress assessment and monitoring. 2) Guidelines for developing academic leadership in the aspect of accuracy, appropriateness, and possibility were at a high level. The guidelines for the development included:  (1) Mission planning, there should be a study on the abilities of personnel to encourage personnel to perform duties with the highest ability. (2) Curriculum and teaching management, there should be a study on context of the center, curriculum, and student instillation in the aspect of professional knowledge to be actually practiced. (3) Teaching supervision, there should be supervision and advice for teachers to develop students and analyze and solve various found problems.  (4) Students’ progress assessment and monitoring, there should be a test of students’ skills, emphasizing on student assessment according to calendar regulations set by academic affairs. (5) Academic atmosphere promotion, there should be promotion on awards and encouragement for personnel by publicizing successful personnel in various media and expanding the operational results within schools.